Analisis Pengaruh Rasio Early Warning System Terhadap Financial Solvency Pada Perusahaan Asuransi Jiwa Syariah Di Indonesia - Ulfan, Kris; Sutriswanto, Sutriswanto; Apriyanto, Gaguk (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to examine the influence of the Early Warning System ratio which consist of surplus change ratio, claim load ratio, cost management ratio, liquidity ratio and premium growth ratio to financial solvency of sharia life insurance company in Indonesia period 2012 - 2016. The data used are secondary data obtained from the website of Asosiasi Asuransi Syariah Indonesia ( AASI ). Sampling technique used in this research is purposive sampling. The sample used in this research is 10 sharia life insurance companies . Hypothesis testing by using multiple linear regression analysis. The results of this study prove that financial solvency at the sharia fairyde 2012 - 2016, with an average value of 507.68% with a minimum financial solvency of 126.83 % and a maximum value of 2447.50 %. The variables that affect the financial solvency in this period of research are the ratio of claims expense and liquidity ratio which shows the negative and significant influence. Surplus change ratios, management expense ratios, the ratio of premium growth proved to be no significant effect on financial solvency . The ratio of Early Warning System in this study proved to have an effect on the financial solvency at the predictive ability level of 25.5% as shown in the adjusted R square value. Other variables not found in this research have influence to financial solvency equal to 74,5%.